Subcutaneous immunoglobulin (SCIG) for maintenance treatment in chronic inflammatory demyelinating polyneuropathy (CIDP), a multicenter randomized double-blind placebo-controlled trial: The PATH Study. Issue 1 (January 2019) - Cocito, D.; Peci, E.; Lauria Pinter, G.; Dacci, P.; Di Muzio, A.; Telese, R.; Schenone, A.; Benedetti, L.; Antonini, G.; Morino, S.; Sorbi, S.; Matà, S.; et al.
Abstract : Several CIDP patients need long-term corticosteroids or intravenous immunoglobulin (IVIG), with IVIG being associated with improved safety profile. SCIG is an alternative option for immunoglobulin delivery but it was not investigated in large-scale trials in CIDP. PATH was a randomized, double-blind trial investigating 0.2 and 0.4 g/kg weekly doses of SCIG IgPro20 (Hizentra®, CSL Behring) versus placebo for maintenance treatment in 172 CIDP patients. IVIG-dependent adults with definite or probable CIDP were eligible. The primary outcome was the percentage of subjects with a CIDP relapse (1-point deterioration on adjusted INCAT disability score) or who were withdrawn for any reason during the 24-week SCIg-treatment. Multiple secondary endpoints were assessed. Overall, 33% of patients on high-dose SCIG, 39% of those on low-dose SCIG and 63% of placebo recipients experienced CIDP relapse or were withdrawn from treatment (p < 0.05 for both SCIG doses vs placebo). INCAT score, MRC sum score, and grip strength remained stable with SCIG, while they deteriorated with placebo. High-dose SCIG prevented R-ODS decline. Adverse events occurred in 47 (27%) patients (18% placebo, 30% low-dose, and 35% high-dose). Both IgPro20 doses were effective and safe as maintenance treatment in patients with CIDP, compared with placebo.